(untitled) (Моделювання, керування та інформаційні технології, 2019)
This paper proposes a model that takes into account the discretization of the Fermi wave vector and energy levels, as well as the condition of electroneutrality when investigating the influence of metal thickness on the spectrum of SPPs waves in heterogeneous dielectric-metal-dielectric structures.